EVALUASI SISTEM PENGADAAN BARANG FASILITAS PERALATAN PRODUKSI MINYAK LEPAS PANTAI, Studi pada CNOOC SES ltd. North Business Unit - , Wahyudi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this research is to evaluate procurement strategyâs implementation by comparing supply activity for offshore equipment maintenance at North Business Unit, CNOOC.SES.LTD in 2009 with the CNOOC.SES.LTD standard procurement manual. This standard procurement manual is consist of spare partsâ price, spare partsâ delivery time, spare partsâ importance and frequency required in 1 year, which will be customized with the standard procurement strategy in CNOOC.SES.LTD, specifically in North Business Unit, and is developed furthermore with criteria : Business Impact and Value, Supplier Positioning, Market Complexity and Value, Supplier Relationship Strategy.